Educational Institutions as a Socio-Political System - Rosi, Fathor; Azisi, Azisi; N, Nurfaiza (STAI Nurul Huda Kapongan Situbondo, 2024)
Educational institutions have a significant role in the socio-political context, as places where the transfer of knowledge, culture, and values is carried out. This article aims to analyze educational institutions as one of the sociopolitical systems, focusing on E. Mark Hanson's conception of schools as entities that affect societal and political change. The research method used is a qualitative approach with a descriptive approach. Data were collected through participatory observation, in-depth interviews, and documentation studies. The results of data analysis show that educational institutions have an important role in strengthening the government's position, influencing national sentiment, and shaping the character of students. The implications of E. Mark Hanson's idea of the school as a sociopolitical system are also discussed. This article is expected to provide a deep insight into the relationship between educational institutions and sociopolitical systems, as well as their relevance in the current context of globalization.